MAKEPUNG DALAM PERSPEKTIF SPORT TOURISM SEBAGAI POTENSI PENGEMBANGAN ATRAKSI WISATA BUDAYA DI KABUPATEN JEMBRANA - Utama, I Putu Sagita Jaya; Murtono, Putu Agus (Jurnal Pariwisata Budaya: Jurnal Ilmiah Pariwisata Agama dan Budaya, 2024)
Jembrana Regency as one of the tourism destinations in Bali has its own uniqueness. Of the many distinctive traditions it has, Jembrana has always been known as ‘Bumi Makepung’. The tradition is an event that always attracts the attention of the community, and is organised in the format of buffalo racing by the local community of Jembrana as a tradition that has been passed down from generation to generation. However, its long-standing existence is still lacking in studies, especially in terms of tourism, both in the form of articles and other literature. The purpose of this article is to enrich the knowledge about makepung and provide an understanding that makepung can be seen as a potential sports tourism attraction wrapped in cultural uniqueness that has the potential to be developed. Through a systematic approach of article review, observation and interviews with Makepung activists, this paper contains views from research sources on makepung, especially from the perspective of sport tourism. Keywords: makepung, sports tourism, cultural tourism.